Quantum Dots for Multiplexed Detection and Characterisation of Prostate Cancer Cells Using a Scanning Near-Field Optical Microscope - Walker, Kelly-Ann D.; Morgan, Claire; Doak, Shareen H.; Dunstan, Peter R. (PLOS ONE, 2012)
In this study scanning near-field optical microscopy (SNOM) has been utilised in conjunction with quantum dot labelling to interrogate the biomolecular composition of cell membranes. The technique overcomes the limits of optical diffraction found in standard fluorescence microscopy and also yields vital topographic information. The technique has been applied to investigate cell-cell adhesion in human epithelial cells. This has been realised through immunofluorescence labelling of the cell-cell adhesion protein E-cadherin. Moreover, a dual labelling protocol has been optimised to facilitate a comparative study of the adhesion mechanisms and the effect of aberrant adhesion protein expression in both healthy and cancerous epithelial cells. This study reports clear differences in the morphology and phenotype of healthy and cancerous cells. In healthy prostate epithelial cells (PNT2), E-cadherin was predominantly located around the cell periphery and within filopodial extensions. The presence of E-cadherin appeared to be enhanced when cell-cell contact was established. In contrast, examination of metastatic prostate adenocarcinoma cells (PC-3) revealed no E-cadherin labelling around the periphery of the cells. This lack of functional E-cadherin in PC-3 cells coincided with a markedly different morphology and PC-3 cells were not found to form close cell-cell associations with their neighbours. We have demonstrated that with a fully optimised sample preparation methodology, multiplexed quantum dot labelling in conjunction with SNOM imaging can be successfully applied to interrogate biomolecular localisation within delicate cellular membranes.